Low-valent cobalt-catalyzed C-C bond formation through imine-directed C-H activation - Xu, Wengang (2017)
Transition metal-catalyzed C–H activation has become a powerful approach for atom- and step-economical synthesis. From a sustainable point of view, the use of earth-abundant transition metals in C–H activation is highly desirable. In this context, cobalt-catalyzed C–H activation has received growing interest. The last several years of research has demonstrated that both low-valent and high-valent cobalt species can be engaged in a variety of C–H functionalization reactions, but still in its infancy. This thesis describes low-valent cobalt-catalyzed C–C bond-forming reactions via directed C–H activation, with a particular focus on the development of novel catalytic systems and directing groups. Chapter 2 reports on a highly linear-selective hydroarylation reaction of styrenes via ketimine-directed C–H activation. The systematic development of a novel triarylphosphine ligand, in combination with fine tuning of other reaction conditions, enabled us to reverse the intrinsic branched selectivity of typical cobalt catalysts in this type of reaction. Chapter 3 describes the use of metallic magnesium as an effective reductant for the cobalt-catalyzed C–H functionalization. While air- and moisture-sensitive Grignard reagents have been typically employed as reductants, the present study has demonstrated that magnesium serves as a viable alternative in a series of imine-directed olefin hydroarylation reactions. Chapters 4–6 report on the utility of N–H imine as a directing group for cobalt-catalyzed C–H functionalization. As described in Chapter 4, this directing group was first identified as a powerful directing group for the hydroarylation of vinylsilane and alkyl olefins. A series of otherwise difficult hydroarylation reactions, including ortho-tetraalkylation of benzophenone imines have been achieved. Chapter 5 describes an extension of the N–H imine-directed hydroarylation to styrene derivatives, where intriguing substrate- or ligand-dependent regioselectivity of C–H activation and C–C bond formation was observed. Finally, Chapter 6 focuses on the use of pivaloyl N–H imine as a transformable directing group. This N–H imine not only efficiently promotes cobalt-catalyzed ortho C–H functionalization reactions with alkyl, aryl, and alkenyl electrophiles, but also readily undergo fragmentation into a nitrile functional group, thus enabling facile preparation of ortho-substituted benzonitriles.